Development of a direct ADR reporting tool for patients to address under-reporting of ADRs to the National Pharmacovigilance Unit in South Africa - Maluleke, Tirhani Lineth (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.